Calcitonin Gene-Related Peptide and Trigeminal Neuralgia - Retsky, Rachel; Ashina, Sait; Oved, Daniel; Sharon, Roni (SN comprehensive clinical medicine, 2023)
Calcitonin gene-related peptide (CGRP) is known to be involved in the pathophysiology of migraine headache. CGRP may play a role in the mechanisms of somatic, visceral, neuropathic, and inflammatory pain. Currently, there are multiple new biologic therapies targeting CGRP which have been approved for the acute and preventive treatment of migraine. Studies have also shown CGRP to be involved in the pathophysiology of trigeminal neuralgia (TN), an often severe and refractory facial pain condition. This article outlines the pathophysiology of trigeminal neuralgia and the role CGRP may play in this condition. We discuss the current evidence on CGRP in trigeminal neuralgia and how modulation of CGRP may be a potential target in the treatment of trigeminal neuralgia in the future. With many similarities in the pathophysiology and efficacy of drug therapies for migraine and trigeminal neuralgia, we hypothesize that targeting CGRP may be a potential mechanism of pain relief in trigeminal neuralgia.